2012
DOI: 10.1371/journal.pcbi.1002800
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Evolution of Peptide Ligands with Custom-Tailored Characteristics for Targeting of Glycostructures

Abstract: As an advanced approach to identify suitable targeting molecules required for various diagnostic and therapeutic interventions, we developed a procedure to devise peptides with customizable features by an iterative computer-assisted optimization strategy. An evolutionary algorithm was utilized to breed peptides in silico and the “fitness” of peptides was determined in an appropriate laboratory in vitro assay. The influence of different evolutional parameters and mechanisms such as mutation rate, crossover prob… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 27 publications
0
16
0
Order By: Relevance
“…The “standard GA parameters” : The “standard GA parameters” are the initial settings for the GA, which we aim to improve in this work. Although the selected values are to some extent arbitrary they are based on previous work reported in the literature . Figure S4 is a schematic showing the design of a typical GA.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The “standard GA parameters” : The “standard GA parameters” are the initial settings for the GA, which we aim to improve in this work. Although the selected values are to some extent arbitrary they are based on previous work reported in the literature . Figure S4 is a schematic showing the design of a typical GA.…”
Section: Resultsmentioning
confidence: 99%
“…Alternative methods use evolutionarily based algorithms. For example, a GA has been used to improve the experimentally based evolution of trypsin‐inhibiting hexapeptides, and an algorithm similar to a GA has facilitated the experimentally based evolution of peptide ligands (containing 16 amino acids) to improve binding to a model target glycostructure (ganglioside G M1 ) …”
Section: Introductionmentioning
confidence: 99%
“…The variation of peptides becomes enormous as the peptides length increases because peptides consist of a combination of 20 natural amino acids (e.g., 1.0 × 10 13 sequences for 10-mer L-peptides). 14 Amino peptidase N (APN or CD13) is a Zn 2+ -dependent metalloprotease that has been implicated in various cell functions, such as proliferation, invasion, and angiogenesis. 14,15 CD13 is highly expressed in various tumor and angiogenic cells.…”
Section: Cyclic Peptide Screening and Optimization Methods Have Beenmentioning
confidence: 99%
“…14 Amino peptidase N (APN or CD13) is a Zn 2+ -dependent metalloprotease that has been implicated in various cell functions, such as proliferation, invasion, and angiogenesis. 14,15 CD13 is highly expressed in various tumor and angiogenic cells. 16 It has also been shown that CD13 is expressed in vascular endothelial cells, such as human umbilical vein endothelial cells (HUVECs), and plays multiple roles in angiogenesis.…”
Section: Cyclic Peptide Screening and Optimization Methods Have Beenmentioning
confidence: 99%
“…Their molecular weight ranges between a typical molecular weight of a small molecule to a protein. Peptide-based drugs also have a high specificity, potency, and low toxicity/limited side effects in the biomolecular recognition processes [15,16]. Furthermore, peptides are part of the components of the defense system found in protozoans, invertebrate, plants, and vertebrate as well as mammals which fight against invaded pathogens such as viruses, bacteria, and fungi by disrupting the orientation of their membrane [17].…”
Section: Introductionmentioning
confidence: 99%